Konsep Pemerintahan Religius dan Demokrasi Menurut Abdul Karim Soroush dan Ayatullah Khomeini - Fadoil, M. Heri (Prodi Siyasah Jinayah (Hukum Tata Negara dan Hukum Pidana Islam) Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2013)
Abstract: Abdul Karim Soroush judges that religious rule is incorrect assessment of the application of Islamic jurisprudence. In a religious society, Islamic jurisprudence obtains the right to govern. It is, of course, necessary to establish a kind of Islamic jurisprudence-based religious rule. Soroush firmly rejects it because such interpretation is too narrow. As for democracy, Soroush argues that the system used is not necessarily equal to that of the Western. On the contrary, Ayatollah Khomeiniâs thoughts on religious rule are reflected in the so called wilayat al-faqih. It is a religious scholar-based government. Democracy, according to him, is the values of Islam itself, which is able to represent the level of a system to bring to the countryâs progress. Principally, there are some similarities between the ideas of Ayatollah Khomeini and those of Abdul Karim Soroush in term of religiosity. They assume that it is able to sustain the religious system of government. The difference between both lies on the application of religiosity itself. Ayatollah Khomeini applies the concept of a religious scholar-based government, while Abdul Karim Soroush rejects the institutionalization of religion in the government or state.Keywords: Governance, democracy, Abdul Karim Soroush, Ayatollah Khomeini